Dukungan Sosial Orangtua dan Efikasi Diri dengan Prokrastinasi Akademik pada Siswa di SMA - Sephia Nur Hanifah; Alif Muarifah (Universitas Negeri Makassar, 2023)
The problem of academic procrastination is very detrimental to the world of education. Academic procrastination is formed from several factors including parental social support and self-efficacy. The purpose of this study was to determine the relationship between parental social support and self-efficacy with academic procrastination in students at SMAN 1 Ngaglik. This research method is quantitative with the research target being class X and XI of SMAN 1 Ngaglik. Sampling used the Proportionate Stratified Random Sampling technique with a total sample of 195 students. The instruments used were the parental social support scale, the efficacy scale, and the academic procrastination scale. Researchers analyzed the data with multiple correlation data analysis techniques and product moment correlation. The results showed that between parents' social support and self-efficacy with academic procrastination showed a sig F Change value of 0.000, for parental social support with procrastination showed a sig value of 0.000, and self-efficacy with academic procrastination in students showed a sig value of 0.000 (p value <0.05). So it can be concluded that there is a negative relationship between parental social support and self-efficacy with academic procrastination in students at SMAN 1 Ngaglik